1970
DOI: 10.3329/jbcps.v26i3.4193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Haemodynamic Status and Arrhythmia between Combined Epidural with General Anaesthesia and General Anaesthesia alone in Off-pump Coronary Artery Bypass (OPCAB) Surgery

Abstract: Objectives: To find out if combined general anaesthesia (GA) with high thoracic epidural anaesthesia (HTEA) was better in controlling haemodynamic condition and reducing incidences of arrhythmia during induction of GA and during positioning and handling of the heart itself by the surgeons. Materials and Method: Forty (40) patients of 40-65 yrs age were randomly selected and divided in two groups (group A, n= 20: combined HTEA and GA- study group, group B, n= 20: GA alone- control group). Group A received HTEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…In this study it was observed that per-operative mean CVP changes at during anastomosis of distal end of the graft with PDA, LCX, D1/D2 and OM1/OM2/OM3 were significantly (p<0.05) higher in group A and others were almost consistent between two groups. On the other hand In this study it was found that per-operative arrhythmia ventricular tachycardia (VT) 10.0% in group A but none was found in group B which is similar with Kundu et al 18 study. Arrhythmia ventricular fibrillation (VF) was 3.3% in group A and none was found in group B, which closely resembles with Bakhtiary et al Study 21 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study it was observed that per-operative mean CVP changes at during anastomosis of distal end of the graft with PDA, LCX, D1/D2 and OM1/OM2/OM3 were significantly (p<0.05) higher in group A and others were almost consistent between two groups. On the other hand In this study it was found that per-operative arrhythmia ventricular tachycardia (VT) 10.0% in group A but none was found in group B which is similar with Kundu et al 18 study. Arrhythmia ventricular fibrillation (VF) was 3.3% in group A and none was found in group B, which closely resembles with Bakhtiary et al Study 21 .…”
Section: Discussionsupporting
confidence: 81%
“…The higher range of the different studies may be due to increased life expectancy in their country.In the current study the male patients was predominant, which is consistent with Kessler et al 1 , Salvi et al 20 and Scott et al 19 studies. In this study it was observed that per-operative mean heart rate changes at wound closure and during anastomosis of distal end of the graft with D1/D2 were not statistically significant (p>0.05), however rest of others times were significantly (p<0.05) less in group B, which is comparable with Kundu et al, Kessler et al, and Salvi et al Studies 18,1,20 . It was found in this current study that per-operative mean of mean arterial pressure (MAP) changes at intubation, skin incision, sternotomy, pericardiotomy were significantly (p<0.05) higher in group A but during anastomosis of distal end of the graft with RCA, PDA, LCX and D1/D2 were ignificantly (p<0.05) higher in group B and others were almost similar between two groups.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We shortlisted 51 RCTs (2112 TEA and 2220 GA) in the meta-analysis (Figure 1). 6,7,20,21,36–82 The pooled age (TEA: 62.8 years; 95% CI, 60.8–64.8 versus GA: 62.7 years; 95% CI, 60.6–64.7), body mass index (BMI; TEA: 27.7; 95% CI, 26.8–28.7 versus GA: 27.9; 95% CI, 26.8–29.0), and left ventricular ejection fraction (LVEF, TEA: 55.1%; 95% CI, 51.8–58.3 versus GA: 54.8%; 95% CI, 49.8–59.8) were similar between both groups. Forty-three studies were solely on coronary artery bypass grafts, while 8 studies included other cardiac surgeries such as valve replacements, including combined coronary artery bypass and valve replacement surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…Kundu et al 18 In this study it is observed that during coronary artery anastomosis in the difficult territories of the heart, anesthetist and surgeon felt more comfort during positioning of the heart and during anastomosis of the graft due to better cardiovascular stabilities in group B.…”
Section: Discussionmentioning
confidence: 94%